Koreografi Tari Piriang Pijak di Ateh Galeh di Nagari Unggan Kecamatan Sumpur Kudus Kabupaten Sijunjung - Adira, Putri Aysiah; Nerosti, Nerosti (Lembaga Yasin AlSys, 2025)
This study aims to describe and analyze the choreography of Tari Piriang Pijak di Ateh Galeh, a traditional dance developed in Nagari Unggan, Sumpur Kudus District, Sijunjung Regency. The research is grounded in the importance of preserving and documenting traditional dance forms as part of local cultural heritage with distinct aesthetic and philosophical values. A qualitative method with a descriptive-analytical approach was employed, where the researcher served as the primary instrument, supported by writing tools and a camera. Data collection techniques included literature review, observation, interviews, and documentation, with data analysis conducted through the stages of data collection, reduction, and conclusion drawing. The findings indicate that the choreography of Tari Piriang Pijak di Ateh Galeh comprises two main aspects: process and form. The choreographic process includes theme selection, exploration, improvisation, and composition. The dance form features nine movement variations, a zigzag floor pattern, spatial designs including curved, high, low, and flat levels, and synchronized group composition involving three dancers. The properties used include plates, candlenuts, glasses, and long cloths, accompanied by traditional musical instruments such as Talempong, Gendang, and Gong. The makeup emphasizes beauty, and the costumes are modified from traditional baju kurung, songket cloth, and supporting accessories. The accompanying music consists of both external and internal elements that enhance the overall performance atmosphere.